2021
DOI: 10.3390/nu13124325
|View full text |Cite
|
Sign up to set email alerts
|

Snack Food Consumption across the Pune Transect in India: A Comparison of Dietary Behaviors Based on Consumer Characteristics and Locations

Abstract: This study examines patterns of snack food consumption (SFC) in the rural-urban-slum transect (RUST) of a large city Pune and its precincts (population 10 million) in India. The transect structure aims to mimic a representative survey for the location capturing differences by age, gender, urbanicity, and socio-economic levels. Dietary data from 1405 individuals were used to describe snacking patterns and other food consumed at different frequencies; extent of physical activity; and Body Mass Index (BMI) and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
3
8
0
Order By: Relevance
“…As reported by a previous study in urban slums, fat food consumption was higher in low socioeconomic neighbourhoods. 23 Because high-fat diets are known to be closely associated with metabolic risks 24 and cardiometabolic risks are rising in low socio-economic groups, added fat consumption needs to be reduced. Our findings are consistent with previous research indicating that Indian diets often lack essential fruits and vegetables, 14 which are critical for addressing widespread micronutrient deficiencies in vitamins A, C and iron, 22 as well as preventing non-communicable diseases such as diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by a previous study in urban slums, fat food consumption was higher in low socioeconomic neighbourhoods. 23 Because high-fat diets are known to be closely associated with metabolic risks 24 and cardiometabolic risks are rising in low socio-economic groups, added fat consumption needs to be reduced. Our findings are consistent with previous research indicating that Indian diets often lack essential fruits and vegetables, 14 which are critical for addressing widespread micronutrient deficiencies in vitamins A, C and iron, 22 as well as preventing non-communicable diseases such as diabetes and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…17 A recent study found high incidence of snack food consumption, including bakery products, savoury and sweet snacks among all age groups, gender, socioeconomic levels in the ninth largest Indian city of Pune. 18 The aim of this paper is to analyse the patterns of processed, including ultraprocessed, food purchases in urban India in greater detail at household level. To do this.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Another study of dietary patterns among factory workers in tier 2 cities of India, Lucknow, Nagpur, Hyderabad and Bangalore, found two of the three distinct dietary patterns associated with high intake of snacks 17. A recent study found high incidence of snack food consumption, including bakery products, savoury and sweet snacks among all age groups, gender, socioeconomic levels in the ninth largest Indian city of Pune 18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roy, Devesh et. all [6] implemented AHP method for comparison of dietary based on consumer location and characteristic.R Miller et. all [7] concluded that Snacks, if added to habitual meal intake, with no compensation for snack energy contribution, are likely over time to lead to positive energy balance.…”
Section: Introductionmentioning
confidence: 99%